The Application behavior of Clean and Healthy Lifestyle of Cooks in the Kitchen Department on Food Quality at Hotel Sibayak Berastagi - Enny Hasriyani (Tourism, Hospitality And Culture Insights Journal, 2021)
The application of clean and healthy living behavior is to improve the quality of health through an educational process which is the beginning of the contribution of each individual in living a clean and healthy daily life. Quality is the totality of facilities and characteristics of a product or service that satisfies a need, expressed or implied. A cook is someone who is in charge of preparing food in the kitchen. This type of research is descriptive analysis, namely the research method by observing the problems that exist at this time. Then, the data were analyzed, the subjects in this study were the cooks in the kitchen department of the Sibayak Berastagi hotel, totaling 12 respondents. Data was collected by giving a questionnaire, which was then processed into data which was then analyzed. The results of the analysis show that the application of clean and healthy living behavior has an impact on food quality, which means that every cook who applies clean and healthy behavior in daily life, both in the home and work environment has an impact on performance. A cook who understands the benefits of implementing PHBS has an impact on the quality of food (especially from the health of the food/products produced), so that when served to guests, a cook feels safe releasing the products served by the restaurant to guests during their stay at the hotel.